The Relationship Between Self-Regulation and Traffic Compliance in High School Students: Hubungan Antara Regulasi Diri dengan Kepatuhan Berlalu Lintas pada Siswa Sekolah Menengah Atas - Punjaya, Very Bagus; Affandi, Ghozali Rusyid (Psikologia : Jurnal Psikologi, 2022)
This study intends to determine the relationship between self-regulation and traffic compliance in class X students of SMA Hang Tuah 5 Sidoarjo. This research is a type of correlational quantitative research. The variables used in this study are self-regulation as the independent variable and traffic compliance as the dependent variable. This research was conducted at SMA Hang Tuah 5 Sidoarjo with a population of 286 students of class X. The sample in this study was 155 students who were taken using the Isaac and Micheal table method with an error rate of 5%. The sampling technique used was non-probability sampling with incidental sampling technique. The data collection technique in this study used a psychological scale with a Likert-scaled model, namely the self-regulation scale and the compliance scale. The hypothesis in this study is that there is a positive relationship between self-regulation and traffic compliance in class X SMA (High School) Hang Tuah 5 Sidoarjo. Data analysis used Pearson Product Moment correlation analysis. The results of the study prove that the correlation value obtained is 0.262 which is a positive value and a significance of 0.001 < 0.05, which means that there is a relationship between Self-Regulation and Traffic Compliance for Hang Tuah 5 Sidoarjo High School students. The results of the R Square test obtained results of 0.068, which means the magnitude of the influence of the Self-Regulation variable on Traffic Compliance is 6.8%. Other results show that most students have a level of Self-Regulation in the moderate category of 41.2%, while the level of Traffic Compliance of students is mostly in the moderate category of 51.6%.